2021
DOI: 10.3390/universe7090331
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Pair Creation in Pulsar Magnetospheres

Abstract: In this paper we study the possibility of efficient pair production in a pulsar’s magnetosphere. It has been shown that by means of relativistic centrifugal force the electrostatic field exponentially amplifies. As a result the field approaches the Schwinger limit leading to a pair creation process in the light cylinder area where the effects of rotation are very efficient. Analysing the parameters of the normal period (∼1 s) pulsars we found that the process is so efficient that the number density of electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In particular, if the electric field reaches the value 1.4×10 14 statvolt cm −1 , efficient pair production will start via the Schwinger mechanism [14]. Therefore, a next step is to consider a similar problem which we have done for pulsars [20] and study pair cascading in AGN magnetospheres.…”
Section: Discusion and Resultsmentioning
confidence: 99%
“…In particular, if the electric field reaches the value 1.4×10 14 statvolt cm −1 , efficient pair production will start via the Schwinger mechanism [14]. Therefore, a next step is to consider a similar problem which we have done for pulsars [20] and study pair cascading in AGN magnetospheres.…”
Section: Discusion and Resultsmentioning
confidence: 99%
“…In a recent paper [3], a new mechanism of pair creation in the magnetospheres of pulsars was presented. In particular, it was shown that since the magnetospheres of pulsars are characterized by rotation, magnetocentrifugal effects might lead to the generation of Langmuir waves.…”
Section: Introductionmentioning
confidence: 99%